The effects of emotional intelligence training on the job performance of Australian aged care workers. Issue 1 (January 2020) - Karimi, Leila; Leggat, Sandra G.; Bartram, Timothy; Rada, Jiri
Abstract : Background: Emotional intelligence (EI) training is popular among human resource practitioners, but there is limited evidence of the impact of such training on health care workers. Purpose: In the current article, we examine the effects of EI training on quality of resident care and worker well-being and psychological empowerment in an Australian aged care facility. We use Bar-On's (1997) conceptualization of EI. Methodology/Approach: We used a quasiexperimental design in 2014–2015 with experimental (training) and control (nontraining) groups of 60 participants in each group in two geographically separate facilities. Our final poststudy sample size was 27 participants for the training group and 17 participants for the control group. Over a 6-month period, we examined whether staff improved their well-being, psychological empowerment, and job performance measured as enhanced quality of care (self-rated and client-rated) by applying skills in EI. Results: The results showed significant improvement among workers in the training group for EI scores, quality of care, general well-being, and psychological empowerment. There were no significant differences for the control group. Practice Implications: Through examining the impact of EI training on staff and residents of an aged care facility, we demonstrate the benefits of EI training for higher quality of care delivery. This study demonstrates the practical process through which EI training can improve the work experiences of aged care workers, as well as the quality of care for residents.